1972
DOI: 10.1002/jso.2930040109
|View full text |Cite
|
Sign up to set email alerts
|

The effect of androgens and estrogens on induced prostatic tumor in the hamster

Abstract: The human adenovirus type 1 2 and the chcmical DMBA inoculated into the prostate of adult hamsters show tumorogenic affects only in the presence of exogcnous administration of estradiol or testosterone. The type of tumor observed was prostatic sarcoma, half of which were differentiated to fibrosarcoma. Castration did not change the incidence of the lesions. The pattern of hormonal influence was related to exogenous estrogen rather than androgen dependcncy when virus or DMBA were administered. Androgen dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1978
1978

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Varkarakis el al. [121], utilizing adult hamsters, found that introduction of human adenovirus type 12, and 7,12-dimethylbenzenthracene produced prostatic tumors, but only in the presence of exogenous estradiol or testosterone. Castration did not affect tumor production.…”
Section: Hormonal Studiesmentioning
confidence: 99%
“…Varkarakis el al. [121], utilizing adult hamsters, found that introduction of human adenovirus type 12, and 7,12-dimethylbenzenthracene produced prostatic tumors, but only in the presence of exogenous estradiol or testosterone. Castration did not affect tumor production.…”
Section: Hormonal Studiesmentioning
confidence: 99%